Amine‐carbon disulfide promoted synthesis of novel benzo[e][1, 3]thiazepin‐5(1H)‐one derivatives. (6th December 2019) - Asgari, Mohammad Sadegh; Bahadorikhalili, Saeed; Asadi, Mehdi; Rashidi Ranjbar, Parviz; Larijani, Bagher; Rahimi, Rahmatollah; Mahdavi, Mohammad
Abstract: In this paper, a simple method is introduced for the synthesis of novel 4‐substituted‐3‐thioxo‐3, 4‐dihydrobenzo[ e ][1, 3]thiazepin‐5(1 H )‐one derivatives. The synthesis is based on a two‐step reaction of 2‐methylbenzoic acid, an amine, and carbon disulfide. In the first step, 2‐methylbenzoic acid reacts with sulfuric acid in ethanol, followed by the reaction with N ‐bromosuccinimide to produce ethyl 2‐(bromomethyl)benzoate. Amine and carbon disulfide react in a separate flask in basic medium to give carbamodithioate salt. Carbamodithioate and ethyl 2‐(bromomethyl)benzoate react together in dimethylformamide to produce the desired 4‐substituted‐3‐thioxo‐3, 4‐dihydrobenzo[ e ][1, 3]thiazepin‐5(1 H )‐one derivatives. The method is simple and fast and is applicable to a wide variety of substrates and gives the desired products in high isolated yields. Abstract :